1996
DOI: 10.1002/art.1780390712
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to fibrillarin in systemic sclerosis (scleroderma). An immunogenetic, serologic, and clinical analysis

Abstract: Objective. To determine the frequency, clinical associations, and any major histocompatibility complex correlations of antifibrillarin antibodies in patients with systemic sclerosis (SSc).Methods. Antifibrillarin antibodies were determined by indirect immunofluorescence, immunoblotting, and immunoprecipitation, and HLA class I1 alleles by DNA oligotyping, in a large cohort of SSc patients.Results. Antifibrillarin was found in 8% of 335 SSc sera and was significantly more common in blacks (16%) than whites (S%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
6
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 47 publications
10
134
6
9
Order By: Relevance
“…Nucleolar staining has been observed in 8-48% of SSc patient sera (6-10), 12-52% of which have been positive for anti-U3 RNP antibodies (6,9,12,13,27,29). Anti-U3 RNP antibodies have been detected in 5-8% of all SSc patients (7,9,(12)(13)(14). Positivity for these antibodies should be suspected in SSc patients with a nucleolar-only staining pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleolar staining has been observed in 8-48% of SSc patient sera (6-10), 12-52% of which have been positive for anti-U3 RNP antibodies (6,9,12,13,27,29). Anti-U3 RNP antibodies have been detected in 5-8% of all SSc patients (7,9,(12)(13)(14). Positivity for these antibodies should be suspected in SSc patients with a nucleolar-only staining pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Antinucleolar antibodies have been detected in 10-15% of SSc patients in different studies (6)(7)(8)(9)(10), and anti-U3 RNP antibody (11) has been previously reported to occur in 5-8% of patients (7,9,(12)(13)(14). Clinical features and prognosis associated with anti-U3 RNP antibodies are not well characterized.…”
mentioning
confidence: 99%
“…Other putative autoantigens that elicit autoantibody responses in patients with SSc include fibrillarin (142), centromere (121), RNA polymerases I, II, and III (1,120), and other nucleolar autoantigens (143). Antifibrillarin antibodies are found in 33% of men with SSc and in 14% of women with SSc and are associated with the HLA-DQB1*0604 and DRB1*1302 haplotypes (142).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 99%
“…The factors triggering the formation of autoreactive B cells against nuclear proteins are still unknown, but genetic, hormonal, and environmental components are involved. A valuable model to study molecular mechanisms of systemic autoimmune responses is mercuryinduced autoimmunity: Chronic administration of mercuric chloride (HgCl 2 ) to susceptible H-2 s mice generates a specific immune response against the nucleolar protein fibrillarin (Hultman et al, 1989;Reuter et al, 1989), which is also a target of antinuclear autoantibodies (ANA) produced by a subset of patients with systemic sclerosis (Arnett et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The factors triggering the formation of autoreactive B cells against nuclear proteins are still unknown, but genetic, hormonal, and environmental components are involved. A valuable model to study molecular mechanisms of systemic autoimmune responses is mercuryinduced autoimmunity: Chronic administration of mercuric chloride (HgCl 2 ) to susceptible H-2 s mice generates a specific immune response against the nucleolar protein fibrillarin (Hultman et al, 1989;Reuter et al, 1989), which is also a target of antinuclear autoantibodies (ANA) produced by a subset of patients with systemic sclerosis (Arnett et al, 1996).Fibrillarin is a 34-kDa protein that derives its name from its localization to both the fibrillar center (FC) and dense fibrillar component (DFC) of the nucleolus (Ochs et al, 1985). The nucleolus constitutes a highly dynamic substructure of the nucleus that forms around ribosome production (Scheer and Hock, 1999;Lewis and Tollervey, 2000;Carmo-Fonseca et al, 2001).…”
mentioning
confidence: 99%